"Among the Boer Children": Australian women teachers in South African concentration camp schools, 1901-1904. Issue 1 (6th June 2016) - Anae, Nicole
Abstract : Purpose: – There exists no detailed account of the 40 Australian women teachers employed within the "concentration camps" established by British forces in the Orange River and Transvaal colonies during the Boer War. The purpose of this paper is to critically respond to this dearth in historiography. Design/methodology/approach: – A large corpus of newspaper accounts represents the richest, most accessible and relatively idiosyncratic source of data concerning this contingent of women. The research paper therefore interprets concomitant print-based media reports of the period as a resource for educational and historiographical data. Findings: – Towards the end of the Boer War in South Africa (1899-1902) a total of 40 Australian female teachers – four from Queensland, six from South Australia, 14 from Victoria and 16 from New South Wales – successfully answered the imperial call conscripting educators for schools within "concentration camps" established by British forces in the Orange River and Transvaal colonies. Women's exclusive participation in this initiative, while ostensibly to teach the Boer children detained within these camps, also exerted an influential effect on the popular consciousness in reimagining cultural ideals about female teachers' professionalism in ideological terms. Research limitations/implications: – One limitation of the study relates to the dearth in official records about Australian women teachers in concentration camps given that; not only are Boer War-related records generally difficult to source; but also that even the existent data is incomplete with many chapters missing completely from record. Therefore, while the data about these women is far from complete, the account in terms of newspaper reports relies on the existent accounts of them typically in cases where their school and community observe their contributions to this military campaign and thus credit them with media publicity. Originality/value: – The paper's originality lies in recovering the involvement of a previously underrepresented contingent of Australian women teachers while simultaneously offering a primary reading of the ideological work this involvement played in influencing the political narrative of Australia's educational involvement in the Boer War.